Assesstment Of Water Quality Around Pengkalan Hulu, Perak - Mohamad, Ikmal Nor Haikal (Universiti Sains Malaysia, 2022)
Numerous elements, including the hydro geochemistry of the study region and anthropogenic activity, have an impact on the water quality in Sungai Pengkalan Hulu, Perak. This study recommends that the anthropogenic activities within Pengkalan Hulu area be monitored as the urbanizations are rapidly taking place and the effects are polluting the water. The purpose of this study was to assess the relationship between the water quality index and the physicochemical parameters (BOD, COD, TSS, ammonia nitrogen, pH, temperature change, and DO) in the surface water of Pengkalan Hulu, Perak. ICP-OES is used to measure the content of heavy metals on the water's surface and WQI) water by the Ministry of Health. Additionally, in order to see the spatial distribution of the researched parameters and observe the pattern of change in this value as a function of the colour space, ArcGIS software was employed in this study. Ten separate sites were used for sampling, and sampling was twice. The data are compared to the MOH and the Water Quality Index (WQI) raw water standards. These parameters are separated into two groups, namely in situ measurements and laboratory measurements. The Pengkalan Hulu river at all stations is considered slightly polluted, except for stations 1 and 2, which are considered clean, based on pH concentration, temperature, dissolvable oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH-3N), and total suspended solids (TSS). According to ICP-OES data, arsenic (As) and cadmium (Cd) contents are extremely low, falling below the value of 0.001 mg/L. The value of other heavy metals, such as copper (Cu) and lead (Pb), varies depending on the station. Thus, it can be concluded that contamination of surface water in Pengkalan Hulu is not just because of the economic activities such as mining industries and logging activities but also due to its mineralization factor.